'Here in India': Nineteenth-Century British Women Navigating their Position in the Empire through Children's Literature. Issue 2 (December 2018) - Aberbach, Jesse
Abstract : This article considers how the children's books written by two nineteenth-century female writers, Eliza Tabor and Mary Martha Sherwood, when they accompanied their husbands to India, enabled them to navigate this new environment and their position as respectable middle-class women while revealing how India was deemed a place where British childhood was impossible. Just as many women took up botanical study to legitimise their 'otherwise transgressive presence in imperial spaces' (McEwan 219), writing for children enabled others to engage with the masculine world of travelling and earning money without compromising their femininity. Addressing their work to children also seems to have helped both writers to deal with the absence of their own children: the Indian climate made it impossibly challenging for most British infants and children. In this way their writing gives expression to what might be termed a crisis of imperial motherhood. Underlying the texts is an anxiety relating to British settlement and an attempt to comprehend and control a place that threatened their maternal roles.